2012
DOI: 10.1002/pros.22514
|View full text |Cite
|
Sign up to set email alerts
|

Serum sarcosine increases the accuracy of prostate cancer detection in patients with total serum PSA less than 4.0 ng/ml

Abstract: We provide evidence that serum sarcosine has a higher predictive value than tPSA and %fPSA in patients with PSA < 4 ng/ml. Moreover, sarcosine levels were significantly different in low grade versus high grade cancers in this subset of patients, suggesting that this marker may be a further tool not only for diagnosing PCa in normal PSA and abnormal DRE/TRUS patients but also for selecting candidates for non-aggressive therapies and active surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 47 publications
9
71
2
1
Order By: Relevance
“…Interest in this molecule was increased in 2009 when Sreekumar and colleagues (19) published their study regarding metabolomic profiles of urine obtained from CaP patients. Even though the linkage of sarcosine with prostate carcinoma development was reported (20,21) as well as its potential in the diagnosis of early-stage tumors (4,22), its use as a marker is still under discussion (23). Hence, it is necessary to study the functions of sarcosine and other amino acids, acting as the intermediate products of metabolism influenced by tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in this molecule was increased in 2009 when Sreekumar and colleagues (19) published their study regarding metabolomic profiles of urine obtained from CaP patients. Even though the linkage of sarcosine with prostate carcinoma development was reported (20,21) as well as its potential in the diagnosis of early-stage tumors (4,22), its use as a marker is still under discussion (23). Hence, it is necessary to study the functions of sarcosine and other amino acids, acting as the intermediate products of metabolism influenced by tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcosine was suggested as a candidate marker for prostate cancer (PCa) [77]; however, its effectiveness has been debated [78,79]. Validations in another sample group indicated that serum sarcosine is more sensitive than PSA among patients with PSA <4 ng/ml [78].…”
Section: Genitourinary Cancermentioning
confidence: 99%
“…Validations in another sample group indicated that serum sarcosine is more sensitive than PSA among patients with PSA <4 ng/ml [78]. Plasma-free fatty acid profiles could be influenced by different pathological states, and multivariate analysis of plasma-free fatty acids could be used as markers to differentiate malignancy (e.g., PCa) from controls [80].…”
Section: Genitourinary Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, the metabolomic approach to this purpose could be relatively easy if we are able to identify one or a few compounds typical of the disease and absent in a healthy status (e.g., the sarcosine in prostate cancer [13]), but could be difficult when these compounds are unknown.…”
mentioning
confidence: 99%